Effectiveness of Honey in Healing Diabetic Foots in Indonesia: Systematic Review - Afriansyah, Rafli; Hidayati, Prema Hapsari; Imran, Muh. (Journal of Midwifery and Nursing, 2024)
Diabetes Mellitus (DM) is a heterogeneous group of disorders characterized by increased blood glucose levels or hyperglycemia. People with DM are prone to developing sores on their feet. Such incidents have been attributed to three factors, namely the presence of sensory neuropathy, ischemia, and high plantar pressure. Therefore, it is critical to treat local wound infections early and aggressively. Wound treatment in Diabetes Mellitus patients can be done with non-pharmacological therapy, one of which is using honey. Honey has antimicrobial, anti-inflammatory effects and increases fibroblastic, angioblastic and has a small water content to speed up the wound healing process. Objective: This research is to determine the effectiveness of honey in diabetic foot therapy. Method: This research uses a Systematic Review based on Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) to identify all published articles using relevant databases and keywords. Results: Based on 25 journals reviewed, the results showed that honey is effective for use as diabetic foot therapy. Conclusion: honey is a good alternative choice in treating diabetic foot wounds. Honey contains antibiotics which function as an antiseptic and antibacterial to protect wounds and can help treat infections that occur in wounds